Model uncertainty in diffusion coefficient for chloride ingress into concrete - Konečný, Petr; Horňáková, Marie; Lehner, Petr; Rovnaníková, Pavla; Sýkora, Miroslav (Elsevier, 2021)
Diffusion coefficient for the chloride ingress into concrete is a key parameter describing the resistance against chloride penetration into the concrete. Consequently, it is an important aspect of the durability of reinforced concrete structures endangered by chloride-induced corrosion. The diffusion coefficient may be used for the direct assessment of the concrete quality with respect to chloride ingress and with respect to the numerical analysis of the durability of reinforced concrete structures. To estimate the diffusion coefficient, the computation based on the Second Fick's Law model and approximation of chloride profile from destructive penetration tests is usually utilised. Semi-destructive or non-destructive electrochemical tests provide estimates of the diffusion coefficient. The study reveals that (a) the resistivity readings provide a higher estimate for diffusion coefficient in comparison to short-time field exposures that seem to be associated with large uncertainty for exposure periods shorter than one year; (b) electrical resistivity measurements show significantly lower variation com-pared to the estimates based on chloride profiles. (C) 2021 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0) Peer-review under responsibility of ICSID 2020 Organizers.

Diffusion coefficient for the chloride ingress into concrete is a key parameter describing the resistance against chloride penetration into the concrete. Consequently, it is an important aspect of the durability of reinforced concrete structures endangered by chloride-induced corrosion. The diffusion coefficient may be used for the direct assessment of the concrete quality with respect to chloride ingress and with respect to the numerical analysis of the durability of reinforced concrete structures. To estimate the diffusion coefficient, the computation based on the Second Fick's Law model and approximation of chloride profile from destructive penetration tests is usually utilised. Semi-destructive or non-destructive electrochemical tests provide estimates of the diffusion coefficient. The study reveals that (a) the resistivity readings provide a higher estimate for diffusion coefficient in comparison to short-time field exposures that seem to be associated with large uncertainty for exposure periods shorter than one year; (b) electrical resistivity measurements show significantly lower variation com-pared to the estimates based on chloride profiles. (C) 2021 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0) Peer-review under responsibility of ICSID 2020 Organizers.
Model uncertainty in diffusion coefficient for chloride ingress into concrete
Keywords: diffusion coefficient; chloride ingress; reinforced concrete structure; electro-chemical tests; calibration; diffusion coefficient; chloride ingress; reinforced concrete structure; electro-chemical tests; calibration